Study the relationship between job satisfaction and organizational commitment / Shazwani Mohd Noor - Mohd Noor, Shazwani (2014)
The purpose of this study is to examine the relationship between job satisfaction and components of organizational commitment among PETRONAS at level 62 which is among HRM-Downstream Technology and Engineering staffs. Therefore this study could make important contribution to extent research in management and organizational behaviour. In the beginning of this study, the purpose, research question, and the need for the study is given. Then, literature is discussed about organizational commitment and job satisfaction that focusing on the relationship between them. The study generated a 96.3 percent response rate from 52 respondents. The result showed that affective, continuance and normative commitment that was found to have significant positive relationship with job satisfaction.